Depiction of Lord Shiva on the northern wall of the Antarala - Temples of India Project Team (Jio Institute, 2024)
Carved on the northern wall of the antarala (vestibule or antechamber) of the Sitaleshwar Temple is the figure of Shiva seated in lalitasana (the royal position or position of royal ease) on a lotus pedestal. Shiva is accompanied by Nandi on his right. Shown with four arms, Shiva holds a trishula (trident) in his upper right hand and a sarpa (snake) in his upper left hand. In his lower right hand, he grasps a pushpa (flower) while his left-hand holds a kamandalu (water carrier or pot). Adorned with jewelry, Shiva, with flowing locks, has a halo behind his head.